FREQUENCY AND CORRELATES OF POOR SLEEP QUALITY AMONG PATIENTS OF PARKINSON’S DISEASE - Kazmi, Syed Sakhawat; Hassan, Zahid; Alamgir, Waseem; Hashmat, Asif; Yousaf, Muhammad Ali; Gilani, Atifa (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the frequency of poor sleep quality among the patients of Parkinson’s disease (PD) and analyze its relationship with the socio-demographic factors. Study Design: Correlational study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, from Jan 2019 to Jun 2019. Methodology: One hundred and fifty patients of Parkinson’s disease were approached to participate in this study. Pittsburgh sleep quality index (PSQI) was the psychometric tool used to assess the study parameter for the patients. Age, gender, duration of illness, poly pharmacy and tobacco smoking were corelated with presence of poor quality of sleep among the patients of Parkinson’s disease. Results: Out of 150 patients of Parkinson’s disease screened through Pittsburgh sleep quality index, 85 (56.7%) showed the presence of poor sleep quality while 65 (43.3%) had good sleep quality. Mean age of the patients was 66.2 ± 4.648 years. After applying the logistic regression, we found that increasing age and longer duration of illness had significant association with the presence of poor sleep quality among the patients of Parkinson disease. Conclusion: Previously considered a pure motor disorder, Parkinsonism has a lot of other neuro-psychiatric manifestations as well. Poor sleep quality turned out to be one of these non-motor problems associated with this chronic debilitating illness. Increasing age and longer duration of illness among these patients emerged as independent risk factors for poor sleep quality in Parkinsonism.